2013
DOI: 10.1111/nph.12156
|View full text |Cite
|
Sign up to set email alerts
|

Allopolyploidy has a moderate impact on restructuring at three contrasting transposable element insertion sites in resynthesized Brassica napus allotetraploids

Abstract: SummaryThe role played by whole-genome duplication (WGD) in evolution and adaptation is particularly well illustrated in allopolyploids, where WGD is concomitant with interspecific hybridization. This 'Genome Shock', usually accompanied by structural and functional modifications, has been associated with the activation of transposable elements (TEs). However, the impact of allopolyploidy on TEs has been studied in only a few polyploid species, and not in Brassica, which has been marked by recurrent polyploidy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 65 publications
2
56
4
Order By: Relevance
“…For example, it is well established that the WGD event caused changes in genome structure among salmonids (Lien et al 2011; Phillips et al 2013), although the reasons behind the variation and its effects on paralog creation and preservation are unclear. We hypothesize that transposable elements are involved in LGD events in S. salar ; it has been shown that post-WGD transposable element activity is highly genome specific in Brassica (Sarilar et al 2013). LGD events have been detected in both trout (Berthelot et al 2014) and chinook salmon (Brieuc et al 2014), but their prevalence is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is well established that the WGD event caused changes in genome structure among salmonids (Lien et al 2011; Phillips et al 2013), although the reasons behind the variation and its effects on paralog creation and preservation are unclear. We hypothesize that transposable elements are involved in LGD events in S. salar ; it has been shown that post-WGD transposable element activity is highly genome specific in Brassica (Sarilar et al 2013). LGD events have been detected in both trout (Berthelot et al 2014) and chinook salmon (Brieuc et al 2014), but their prevalence is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the natural allopolyploid Spartina anglica , evidence of major changes in CpG methylation in the proximity of retrotransposon insertions were found by sequence-specific amplified polymorphism (SSAP) analysis; however, few new TE insertions were proposed among the retrotransposon families investigated (terminal-repeat retrotransposons in miniature, Cassandra and Wis Copia -like retrotransposons) [Parisod et al, 2009], although some fragment losses were detected immediately after hybridisation [Parisod et al, 2010a]. More recently, a study of Athilalike retrotransposons by SSAP in the synthetic allotetraploids B. napus revealed mostly additive profiles when compared with the diploid parents, and the characterisation of nonadditive SSAP bands indicated that genomic rearrangements had occurred rather than new transposition events [Sarilar et al, 2013]. Similar analyses revealed a proliferation of the Tnt 1 retrotransposon after genome doubling in the synthetic Nicotiana tabacum .…”
Section: Retrotransposons Are Involved In Polyploidisationassociatedmentioning
confidence: 99%
“…The simultaneous mutation in two different genes cannot be explained from the position of random mutagenesis. Over the past 10 to 15 years, a number of literature sources have proven that plant genomes whose origin is associated with allopolyploidization or wide hybridization are prone to some processes that could be interpreted as destabilization of such genomes [24,25,27]. On the phenotypic level, this means the emergence of new traits which were not present in the parent lines [39], new gene alleles of storage proteins [40,41], and material changes in the gene expression [42,43], right up to gene silencing [44].…”
Section: Iw2(ò)iw ²W3(ò)iw3(ò)mentioning
confidence: 99%
“…In recent literature, significant attention is given to the processes occurring in natural and artificial amphidiploids during formation of their genomes [21][22][23][24][25][26][27]. It seems that the Aurotica genome, which has an introgressive origin, possesses some process resulting in the mutation of the dominant allele into a recessive one at a rate significantly higher than the known average rate of spontaneous mutation per gene per generation.…”
Section: Introductionmentioning
confidence: 99%